The divided family in Civil War America - Taylor, Amy Murrell (Civil War America (Series), 2005)
Taylor looks behind the Civil War metaphor of "brother against brother" to the real experiences of families, particularly in border states, whose households were split by divided loyalties. She studies letters and diaries to understand how families coped with division between husbands and wives, fathers and sons, and she traces the adoption of the image of the "house divided" in newspapers, government documents, and popular fiction to describe the divided nation.